Microstrip yagi antenna for ALMA band 11 receiver - Tan, B; Yassin, G; Whithington, S; Goldie, D (2019)
We present a planar Yagi antenna that has an end-fire beam characteristic and broad operational bandwidth. Two dipoles with different lengths are cascaded together to broaden the bandwidth. Printed directors and truncated ground plane are employed to achieve high front-to-back gain ratio. The double-dipole antenna is fed directly with a microstrip, and hence is readily adaptable to most of the millimetre and sub-millimetre detector circuits. In this paper, we present the antenna design in the context of designing a 1.05 THz Superconductor-Insulator-Superconductor (SIS) mixer that is suitable for Atacama Large Millimetre/Sub-millimetre Array (ALMA) Band 11 receiver. Detailed analysis of the antenna design is discussed, and simulated far field beam patterns and bandwidth performance is presented.